2019
DOI: 10.3389/fpsyt.2019.00696
|View full text |Cite
|
Sign up to set email alerts
|

Frequent Bullying Involvement and Brain Morphology in Children

Abstract: Background: Over the past few decades, bullying has been recognized as a considerable public health concern. Involvement in bullying is associated with poor long-term social and psychiatric outcomes for both perpetrators and targets of bullying. Despite this concerning prognosis, few studies have investigated possible neurobiological correlates of bullying involvement that may explain the long-term impact of bullying. Cortical thickness is ideally suited for examining deviations in typical brain development, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 62 publications
(81 citation statements)
references
References 59 publications
3
77
0
1
Order By: Relevance
“…Image processing and quality assessment T 1 -weighted images were processed using FreeSurfer Software, version 6.0 (http://surfe r.nmr.mgh.harva rd.edu). The technical details of these procedures are described elsewhere (Muetzel et al 2019). In brief, this included removal of the non-brain tissue, Talairach transformation, segmentation of white and grey matter structures, tessellation of the greywhite matter boundary, topology correction and surface deformation to identify the cortical grey-white matter boundary and the grey-cerebrospinal fluid boundary.…”
Section: Mri Data Acquisitionmentioning
confidence: 99%
“…Image processing and quality assessment T 1 -weighted images were processed using FreeSurfer Software, version 6.0 (http://surfe r.nmr.mgh.harva rd.edu). The technical details of these procedures are described elsewhere (Muetzel et al 2019). In brief, this included removal of the non-brain tissue, Talairach transformation, segmentation of white and grey matter structures, tessellation of the greywhite matter boundary, topology correction and surface deformation to identify the cortical grey-white matter boundary and the grey-cerebrospinal fluid boundary.…”
Section: Mri Data Acquisitionmentioning
confidence: 99%
“…FreeSurfer image reconstructions of the T1-weighted images were visually inspected for quality. All scans rated as unusable were excluded from statistical analyses ( Muetzel et al, 2019 ). Diffusion image quality was assessed by manual inspection (visualization of residual error maps from the tensor fit and inter-subject registration) and automated methods (DTIprep toolkit, https://www.nitrc.org/projects/dtiprep ) ( Muetzel et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, a review on traditional bullying in young people found that the brain experiences peer victimization in a similar way to physical pain, and that these experiences can become biologically embedded in the physiology of the developing person, thereby increasing their risk of developing mental health problems ( Vaillancourt et al, 2013 ). Recently, Muetzel et al (2019) conducted a study of 2,602 children regarding traditionally bullying, and involved the 8-year-old children, their parents and teachers reporting on common forms of child bullying involvement (physical, verbal, and relational), and then completing a structural MRI scans when the children were 10 years old. The study found that those children who were frequently bullied had thicker cortex in the fusiform gyrus, a region suggested to be implicated in a wide array of functions, including facial and emotion processing, language, and theory of mind ( Muetzel et al, 2019 ).…”
Section: Cyberbullying and The Brainmentioning
confidence: 99%
“…Recently, Muetzel et al (2019) conducted a study of 2,602 children regarding traditionally bullying, and involved the 8-year-old children, their parents and teachers reporting on common forms of child bullying involvement (physical, verbal, and relational), and then completing a structural MRI scans when the children were 10 years old. The study found that those children who were frequently bullied had thicker cortex in the fusiform gyrus, a region suggested to be implicated in a wide array of functions, including facial and emotion processing, language, and theory of mind ( Muetzel et al, 2019 ). Whilst these aforementioned studies shed light on how victims of bullying perceive their bullies and highlights that frequent bullying could affect brain development, further research is needed which focuses on cyberbullying specifically, as well as over time.…”
Section: Cyberbullying and The Brainmentioning
confidence: 99%